Developing middle school students’ computational thinking skills using unplugged computing activities - Delal, Havva. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
This study investigated the role of unplugged computing activities on developing computational thinking (CT) skills of 6th grade students. The unplugged computing classroom activities were based on Bebras challenges. Bebras, an international organization, aims to promote informatics and CT among school students. Participants of the study were 6th grade (n=24 female and n=29 male) students from two public middle schools in Istanbul. The activities in the study were divided into three  groups  as  “easy”,  “medium”  and  “difficult”  according  to  the difficulty levels as defined in the Bebras competition, which were selected so that each group involved four components of CT skills found to be common in CT definitions in the literature -- abstraction, decomposition, algorithmic thinking, and generalization. To evaluate students’  CT  skills,  two  equivalent tests were prepared. Questions in these tests were also selected from Bebras and translated into Turkish. Also, questions in the tests have three difficulty levels and covers the four major CT skills as in the activities. These tests were used as a pre-test and post-test, and their results were compared to assess  students’  CT  skill development. The CT Scale (Korkmaz et al., 2016) was also given to the participants at the end of the instruction. The results of the study showed that students’  post-test scores were significantly higher than pre-test scores. However, there was not any significant differences between  students’  scores  in  terms   of gender, and there was  no  interaction  effect  between  students’  scores  and their gender. In terms of the CT Scale results, there was no significant difference between male  and  female  students’  self-evaluation of CT skill
Keywords: Middle school students.; Information technology -- Middle school students.